2006
DOI: 10.1016/j.ijid.2006.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient phylogenetic analysis may not exclude candidacy of typhoid fever as a probable cause of the Plague of Athens (reply to Shapiro et al.)

Abstract: 4 ), the recommendation of phylogenetic verification of results continues to be ignored, despite the relative simplicity and lack of expense of such tests, particularly in comparison to experimental procedures. It should be noted that many of the most embarrassing mistakes in the ancient DNA literature (including the incorrect report of dinosaur DNA in the early 1990s 5 ) could have been avoided with a simple phylogenetic test.Conflict of interest: No conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
4
0
3
Order By: Relevance
“…96 Moreover, it is generally agreed that Athens was probably suffering from outbreaks of multiple diseases, and there is no proof that typhoid fever was the disease associated with the ''plague'' outbreak. 97,98 Pathogens evolve, as does host response, and other critics argue that the epidemiology of the epidemic is inconsistent with typhoid fever, 99 although possible differences between the ancient and modern strains of the pathogen might make it hard to rely too much on analogies to modern epidemiologic patterns.…”
Section: ''Primitive'' Warfarementioning
confidence: 99%
“…96 Moreover, it is generally agreed that Athens was probably suffering from outbreaks of multiple diseases, and there is no proof that typhoid fever was the disease associated with the ''plague'' outbreak. 97,98 Pathogens evolve, as does host response, and other critics argue that the epidemiology of the epidemic is inconsistent with typhoid fever, 99 although possible differences between the ancient and modern strains of the pathogen might make it hard to rely too much on analogies to modern epidemiologic patterns.…”
Section: ''Primitive'' Warfarementioning
confidence: 99%
“…El descubrimiento de una fosa común en los terrenos del muy antiguo cementerio Kerameikos (Figura 2), durante la excavación de una estación de metro mientras Atenas se preparaba para las olimpíadas del 2004, reveló los restos de unos 150 niños, mujeres y hombres, enterrados en forma progresivamente apresurada y desordenada, sin evidencia del cuidadoso ceremonial fúnebre como era la costumbre de los atenienses, y con cerámica votiva estimada del año 430 a.C. De la pulpa dentaria de tres osamentas se aisló ADN que fue identifi cado como Salmonella enterica serovar Typhi. Los autores concluyen que este podría ser el agente causal de la peste [28][29][30] . El hallazgo y sus conclusiones han sido controvertidos 31 , y no han sido replicados hasta ahora.…”
Section: Diagnóstico Diferencialunclassified
“…Shapiro et al further suggested that the sequence might have come from soil surrounding the burial and that the analysis is therefore compromised. Papagrigorakis et al 45 responded that soil wash was used as a negative control and that there was no contamination, a phylogenetic analysis of only 1 gene might be insufficient or misleading, and Salmonella species do not survive for long in soil. A DNA analysis of the skeletal materials is an intriguing start that one could anticipate will lead to new information about paleopathology and the plague years.…”
Section: Paleopathologymentioning
confidence: 99%